2018
DOI: 10.5507/bp.2018.022
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal delivery systems of antihypertensive drugs: A practical approach in general practice

Abstract: Patients who are unable to receive oral medication (p.o.) are a major problem in outpatient settings, especially in home health care systems. Mucosal administration of drugs offers an alternative to the oral route, especially when the parenteral mode cannot be used. There are three main pathways of mucosal administration: sublingual/buccal, intranasal and rectal. We discuss the possibility of mucosal delivery of antihypertensive drugs. Perindopril arginine and Amlodipine besylate are registered in the EU as or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…A limitation to this study is that we cannot show definitive absorption of the sublingual supplement. However, sublingual routes of drug delivery are established in pharmacokinetic studies 19,20 . Recent research presented by Satia and colleagues found superior sublingual absorption compared to capsules in patients with malabsorption issues 21 preparations.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A limitation to this study is that we cannot show definitive absorption of the sublingual supplement. However, sublingual routes of drug delivery are established in pharmacokinetic studies 19,20 . Recent research presented by Satia and colleagues found superior sublingual absorption compared to capsules in patients with malabsorption issues 21 preparations.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A recent review has studied the sublingual/buccal and rectal administration of antihypertensive drugs, with the sublingual administration of perindopril and captopril being of the most clinical interest for our case. 10 While perindopril is a prodrug and needs to be activated in the liver into the active metabolite, captopril is not, which may result in faster absorption and higher bioavailability. 10 Sublingually administered drugs reach the systemic circulation by diffusing through the highly vascularized mucosa of the oral cavity, thereby bypassing the gastrointestinal tract and first-pass metabolism in the liver.…”
Section: Discussionmentioning
confidence: 99%
“… 10 While perindopril is a prodrug and needs to be activated in the liver into the active metabolite, captopril is not, which may result in faster absorption and higher bioavailability. 10 Sublingually administered drugs reach the systemic circulation by diffusing through the highly vascularized mucosa of the oral cavity, thereby bypassing the gastrointestinal tract and first-pass metabolism in the liver. 11 Pharmacokinetic studies of captopril have shown a shorter T max (45 vs. 75 min) for the sublingual administration compared to oral administration, with no significant difference in C max and area under the curve.…”
Section: Discussionmentioning
confidence: 99%
“…As the development of appropriate formulations for kids is a major challenge, various studies have focused on developing new dosage forms for propranolol hydrochloride including buccal formulations in an attempt to overcome these problems. [1][2][3][4] The buccal route has been regularly adopted for the systemic delivery of drugs experiencing hepatic first-pass metabolism 5 or to extend drug release. 6 This route has arisen as an attractive site for pediatrics systemic drug administration.…”
Section: Introductionmentioning
confidence: 99%